The Relationship Between Financial Performance and Profitability: An ROA and EPS Approach in the Food and Beverage Industry - Pertiwi Harkitianis Murti; Anke Dwi Lestari; Farah Margaretha Leon (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to identify factors influencing profitability in the food and beverage sector listed on the Indonesia Stock Exchange. The novelty of this research lies in the inclusion of sales growth as an independent variable. The study uses panel data from 22 companies over the 2020–2024 period, totaling 110 observations. Data analysis is conducted using panel regression and Ordinary Least Squares (OLS) methods. The OLS results show that liquidity, sales growth, efficiency, and firm size positively affect ROA, while working capital and leverage have negative effects. The panel model finds that only sales growth significantly affects ROA. For EPS, OLS shows working capital, efficiency, and size as significant, while panel regression finds working capital and efficiency positive, and inflation negative. Other variables are not significant. These findings suggest that managers should improve efficiency and scale, while investors should prioritize firms with strong assets and efficient operations to enhance profitability.